2017
DOI: 10.5664/jcsm.6466
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in OEF/OIF/OND Veterans: Associations with PTSD, Personality, and Coping

Abstract: Study Objectives: Sleep disturbances are well documented in relation to trauma exposure and posttraumatic stress disorder (PTSD), but correlates of such disturbances remain understudied in veteran populations. We conducted a preliminary study of sleep disturbances in Operation Enduring Freedom, Operation Iraqi Freedom, and Operation New Dawn veterans (n = 133; mean [standard deviation] age = 29.8 [4.7] y). Methods: Veterans were assigned to one of three groups based on responses to the Clinician Administered P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…For the present study, data was used from those participants who had a history of a Criterion A combat trauma event during OIF/OEF/OND deployment, assessed as part of the clinical interview with the Life Events Checklist (LEC; Gray, Litz, Hsu, & Lombardo, 2004) and who met certain criteria (described in the Measures section) as part of the Clinician Administered PTSD Scale (CAPS) DSM-IV version (Blake et al, 1995). To date, published work from this study has examined the relationship between PTSD and disturbed sleep (Lind et al, 2017), and additional work under review has examined anxiety sensitivity and distress tolerance. Thus, the current work is the first from this study to examine negative cognitions and their interplay with coping behaviors on PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…For the present study, data was used from those participants who had a history of a Criterion A combat trauma event during OIF/OEF/OND deployment, assessed as part of the clinical interview with the Life Events Checklist (LEC; Gray, Litz, Hsu, & Lombardo, 2004) and who met certain criteria (described in the Measures section) as part of the Clinician Administered PTSD Scale (CAPS) DSM-IV version (Blake et al, 1995). To date, published work from this study has examined the relationship between PTSD and disturbed sleep (Lind et al, 2017), and additional work under review has examined anxiety sensitivity and distress tolerance. Thus, the current work is the first from this study to examine negative cognitions and their interplay with coping behaviors on PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with PTSD experience more arousals from sleep (Capaldi et al., ), sleep for shorter amounts of time (Seelig et al., ), and report worse quality sleep (King et al., ; Lind et al., ) than those without PTSD. Indeed, trouble falling or staying asleep is the most commonly reported symptom of PTSD after deployment (McLay et al., ) and persists following effective treatment of PTSD (Zayfert and Deviva, ).…”
Section: Ptsd and Alcohol Problemsmentioning
confidence: 99%
“…Sleep problems are common symptoms of stress-related and mood disorders; in fact sleep disturbance is part of the symptom criteria for both PTSD and MDD, but studies on mild TBI and sleep often do not control for mental health co-morbidities (Gosselin et al., 2009; Williams et al., 2008). Among Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF)/Operation New Dawn (OND) veterans, those with PTSD reported worse sleep than trauma-exposed controls (Lind et al., 2017), and controlling for PTSD symptoms removed the reported sleep difference between PTSD only and PTSD + TBI groups, suggesting that greater PTSD symptoms drove the higher scores in the PTSD + TBI comorbid group (DeGutis et al., 2018). A longitudinal study of change in sleep over time among OEF/OIF veterans with PTSD showed that nightmares increased over time although overall sleep complaints decreased (King, Donnelly, Warner, Wade, & Pigeon, 2017).…”
Section: Introductionmentioning
confidence: 99%